Research progress of spontaneous ruptured hepatocellular carcinoma: Systematic review and meta-analysis - Wang, Chunling; Huang, Xiaozhun; Lan, Xiaofeng; Lan, Dongmei; Huang, Zhangkan; Ye, Shu; Ran, Yihong; Bi, Xinyu; Zhou, Jianguo; Che, Xu (Frontiers in Oncology, 2022)
Background: Spontaneously ruptured hepatocellular carcinoma (rHCC) with hemorrhage is characterized by rapid onset and progression. The pathogenesis is unclear, and the functional status of the liver in rHCC patients is complex. Since there is considerable heterogeneity between the survival benefits conferred by the different treatment strategies, it is often difficult to make the optimum clinical decision. Therefore, it is critical to identify novel prognostic indicators or models in order to predict the treatment outcomes in patients with rHCC. The aim of this systematic review was to explore the current studies on rHCC with hemorrhage and determine the optimum treatment strategy. Method: The PubMed, Web of Science, Embase, and the Cochrane Library databases were searched for studies reporting survival outcomes of HCC rupture. The perioperative and survival data were statistically summarized using Review Manager 5.3 software and Stata 12.0 software. Result: We discussed the rupture mechanism of HCC and the operation time of high burst tendency HCC, and conducted a meta-analysis on the efficacy and safety of ER and SH in treating spontaneous rHCC. The results showed that there was no significant difference in the short-term efficacy of either approach in the treatment of rHCC, while SH was superior to ER in terms of long-term survival. Therefore, different treatments of short- and long-term survival benefit with multiple model prediction effect for the treatment of rHCC. Finally, we explored the treatment of rHCC survivors. Conclusion: A better understanding of the indicators or models associated with treatment outcomes of patients with rHCC may help guide treatment decisions.